ANALISIS SINONIMI TIGA LEKSEM PENANDA WAKTU DALAM BAHASA JEPANG - Yogyanti, Devita Widyaningtyas (Kajian Linguistik dan Sastra, 2019)
This article discusses the semantics, of three Japanese time signifiers, namely toki, sai, and atatte. Those lexemes are synonymous. However, in particular context, they are not interchangeable. This research aims to (1) find the meaning of those three lexemes, (2) to investigate the difference among those three, and (3) to describe why those lexemes appear in Japanese vocabulary. The meaning component is analyzed using interview and reference studies method. After that, meaning component of those lexeme is analyzed using substitution method to find the difference. The result of this research is that those three lexemes have the same sense as lexeme that related to time. In addition, those three lexemes have common component that are jikoku (when or time) and formality. Yet, in other contexts those lexemes are not interchangeable because each lexeme has supplement component that becomes its characteristic. This supplement component causes those three lexemes to be not interchangeable in some particular contexts. The needs of special meaning of those three lexemes in a sentence causing those lexemes exist in Japanese vocabulary.Keywords: Japanese, time signifier, toki, sai, atatte, synonym